Konsep Dasar Adh-Dhaman (Penjaminan) - Rizki Eliana; Musyrifah Salmi; Fatmah Taufik Hidayat (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Adh-dhaman is an essential concept in Islamic law, particularly related to liability and obligations for damages or harm caused by an individual to the property or rights of others. The term originates from the Arabic word dhimmah, which means responsibility or obligation, and has broad applications in the context of muamalah (social and business interactions). The legal basis for Adh-dhaman in Islamic law is found in both the Qur'an and the sayings of Prophet Muhammad (peace be upon him). In the Qur'an, Allah says,